Comunicación interna y compromiso organizacional de los trabajadores en la Municipalidad Provincial de Maynas 2025 - Wong Luján, Gissela (2025)
This research aimed to determine the relationship between internal communication and organizational commitment among employees at the Provincial Municipality of Maynas, 2025. The study was basic, non experimental, cross-sectional. The sample consisted of 65 employees. In the results, in the Internal Communication variable, 16.9% responded that internal communication is poor and 46.2% stated that internal communication is good among workers in the Provincial Municipality of Maynas, 2025. In the Organizational Commitment variable, 10.8% provided a response that organizational commitment is poor, and 47.7% stated that the organizational commitment of workers in the Provincial Municipality of Maynas, 2025 is good. In addition, the chi-square test showed a significance value of 0.000<0.05, indicating that there is a significant relationship between internal communication and organizational commitment of workers in the Provincial Municipality of Maynas, 2025.